PENGARUH BEBERAPA METODE PERENDAMAN TERHADAP PEMATAHAN DORMANSI BENIH PADI (Oryza sativa L.) VARIETAS CIHERANG - Ni Luh Rai Yuli Ardani; Anak Agung Made Astiningsih; Ni Luh Made Pradnyawathi (UPN VETERAN JAWA TIMUR, 2022)
This study aims to determine the effect of several immersion methods on dormancy breaking and methods that can accelerate dormancy breaking of Ciherang rice seeds. The experimental design used was a one-factor completely randomized design, namely the immersion method with 5 levels of treatments: the non-immersion method (P0), the immersion method using water at 30°C for 24 hours (P1), the immersion method using hot water with an initial temperature of 60°C for 24 hours. 24 hours (P2), the immersion method used a GA3 solution with a concentration of 0.5 ppm for 24 hours (P3), and the immersion method used a 3% KNO3 solution for 48 hours (P4) with five replications. The research was conducted at the Laboratory of Plant Breeding and Seed Technology, Faculty of Agriculture, Udayana University from September 2020 to November 2020. The results showed that the immersion method had a very significant effect on the germination variable (%), maximum growth potential (%), dormancy intensity (%), and speed of germination (%/etmal), and significantly affect the growth of seed fungus (%). P3 treatment was able to break the dormancy of rice seeds for 5 weeks of observation with the highest germination value (95.16%) and obtained the smallest dormancy intensity value (4.56%) better than P0 treatment without soaking (control) obtained a germination value of (7.76%) and the value of dormancy intensity (89.52%). The highest germination rate was obtained in treatments P3 and P4, which were (6.08%/etmal) and (3.35%/etmal, respectively).